Preparation of Metal Immobilized Orange Waste Gel for Arsenic(V) Removal From Water - Biplob Kumar Biswas; Katsutoshi Inoue; Keisuke Ohto; Hiroyuki Harada; Hidetaka Kawakita (Aceh International Journal of Science and Technology, 2014)
Abstract - The toxicity of arsenic is known to be a risk to aquatic flora and fauna and to human health even in relatively low concentration. In this research an adsorption gel was prepared from agricultural waste material (orange waste) through simple chemical modification in the view to remove arsenic (V) from water. Orange waste was crushed into small particles and saponified with Ca(OH)2 to prepare saponified orange waste, which was further modified by immobilizing gadolinium(III) to obtain desired adsorption material (Gd(III)-immobilized SOW gel). The effective pH range for arsenic adsorption was found to be 7.5 – 8.5. Adsorption capacity of the gel was evaluated to be 0.45 mol-arsenic (V)/kg. Dynamic adsorption of arsenic (V) in column-mode was conducted and a dynamic capacity was found to be 0.39 mol/kg. Elution of arsenate was tested after complete saturation of the column packed with gadolinium-immobilized orange waste adsorption gel. A complete elution of arsenate was achieved with the help of 1 M HCl and 28 times pre-concentration factor was attained. This study showed that a cheap and abundant agro-industrial waste material could be successfully employed for the remediation of arsenic pollution in aquatic environment.Keywords: Arsenic; Orange waste; Gadolinium(III); Adsorption; Elution.